2006
DOI: 10.1523/jneurosci.2805-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Dependent Plasticity in the Olfactory Intrabulbar Map

Abstract: In mammals, each olfactory bulb contains two mirror-symmetric glomerular maps. Isofunctional glomeruli within each bulb are specifically linked through a set of reciprocal intrabulbar projections (IBPs) to form an intrabulbar map. We injected neural tracers into the glomerular layer on one side of the bulb and examined the resulting projection on the opposite side. In adult mice, the size of the projection tuft is directly proportional to the size of the injected region. Using this ratio as a measure of IBP ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
54
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 42 publications
10
54
0
Order By: Relevance
“…As with many other systems (Erzurumlu and Kind, 2001; Espinosa and Stryker, 2012; Marks et al, 2006; Walsh and Lichtman, 2003), postnatal remodeling is likely required for the formation of a mature taste bud with appropriate connections between taste receptor cells and gustatory neurons (Kinnamon et al, 2005; Mistretta et al, 1988; Nagai et al, 1988; Yuan and Yankner, 2000). BDNF regulates this remodeling in other systems (Cabelli et al, 1997; Gonzalez et al, 1999; Kaneko et al, 2008), and in the gustatory system is expressed in postnatal and adult taste buds (Huang and Krimm, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…As with many other systems (Erzurumlu and Kind, 2001; Espinosa and Stryker, 2012; Marks et al, 2006; Walsh and Lichtman, 2003), postnatal remodeling is likely required for the formation of a mature taste bud with appropriate connections between taste receptor cells and gustatory neurons (Kinnamon et al, 2005; Mistretta et al, 1988; Nagai et al, 1988; Yuan and Yankner, 2000). BDNF regulates this remodeling in other systems (Cabelli et al, 1997; Gonzalez et al, 1999; Kaneko et al, 2008), and in the gustatory system is expressed in postnatal and adult taste buds (Huang and Krimm, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that coarse topography of intrabulbar projection is formed in an activity-independent manner; however, refinement to establish the precise connectivity requires sensory-evoked activity [73]. Unlike other sensory systems, there is no critical period for this activity-dependent refinement process, i.e., plasticity persists throughout life.…”
Section: Intrabulbar Projection Of Tufted Cellsmentioning
confidence: 99%
“…Enhancing odorant-induced activity with odorant conditioning during development has been shown to accelerate the refinement of both glomerular (Kerr and Belluscio, 2006) and intrabulbar circuitry (Marks et al, 2006). Long-term naris closure causes altered glomerular refinement if it begins soon after birth (Nakatani et al, 2003; Zou et al, 2004), but not when initiated later in life.…”
Section: Introductionmentioning
confidence: 99%
“…These projections connect isofunctional odor columns through synapses in the internal plexiform layer (IPL) to produce an intrabulbar map. Developmental studies show that initially intrabulbar projections broadly target the IPL on the opposite side of the bulb and refine postnatally to their adult precision by 7 weeks of age in an activity-dependent manner (Marks et al, 2006). In this study, we sought to determine the capacity of intrabulbar map to recover its precision after disruption.…”
mentioning
confidence: 99%